KAJIAN BUSINESS PROCESS RE-ENGINEERING SISTEM INFORMASI PERPUSTAKAAN: STUDI KASUS INSTITUT TEKNOLOGI DEL - Lumban Gaol, Tiurma (BACA: Jurnal Dokumentasi dan Informasi, 2015)
The development of today’s technology requires libraries to follow the development of existing technologies. Existing information systems must continually be developed to adjust to the evolving needs and developments in information technology. Del Technology Institute as an institution must constantly develop technology-based information systems with either one of them is the library information system. Currently the library information system ITD require development so as to answer the needs of the system at management level. ITD library information systems need to be developed as a knowledge portal and can be accessed using a mobile phone. Besides institutional repository is also an important part that must be provided at the library information system. Therefore, the business process reengineering is a very important part to develop information systems.